Molecular and Cellular Body Composition Components Predict Sprint Performance in Adolescents - Correas-Gómez, Lorena; Alvero-Cruz, José Ramón; Carrillo-de-Albornoz, Margarita; Fernández-García, José Carlos; Martín Sanz, Norma Teresa; Álvarez-Carnero, Elvis (Medicine & Science in Sports & Exercise, American College of Sports Medicine, 2014)
Body composition including hydration has been classically associated with aerobic performance. However, the relationships between anaerobic performance assessed by sprints and hydration have not been analyzed extensively in the literature, particularly among children and adolescents. This is a paradoxical situation because the child is primarily involved in short-term high intensity exercise in almost daily tasks, games or sports events. The analysis of these associations must be useful to describe the importance of hydration and lean mass for performance in healthy adolescents. PURPOSE: To analyze the association between 30m-sprint test and body composition (BC) variables in young athletes and non-athletes. METHODS: BC was assessed by anthropometric measures and total-body bioelectrical impedance analysis (BIA) in 159 adolescents between 12 and 18 years old (15.0 ± 1.5 yrs, BMI = 21.1 ± 3.5 kg/m2 ). The volunteers were recruited from local high-schools and local sport clubs. Athletes (AT) and non-athletes (NAT) were identified using ad hoc questionnaire (NAT = 101, 41 boys, 60 girls, and AT = 58, 27 boys, 31 girls). Body fat (BF) and fat free mass (FFM) were calculated by anthropometric derivedequation. Total body water and intracellular water (ICW) were obtained from BIA. Photoelectrical cells were used to measure time spent in 30-m. Partial correlations were carried out to determine associations between BC variables and 30-m sprint values. The best-correlated variables with sprint performance were included in a stepwise regression analysis to determine BC predictors of sprint performance. RESULTS: As expected AT were faster than NAT in 30-m (5.07 ± 0.47 vs 5.52 ± 0.59 sec, P<0.001), but there were no significant differences in ICW (AT = 16.0 ± 5.1 vs NAT = 14.7 ± 6.1%, P>0.05). A significant correlation was found between ICW and 30m-sprint test after controlled by age and kg of BF (r = -0.732, P<0.001). When subjects were pooled together, %FFM, ICW, age and the athlete condition were predictors of the 30-m run (R2 = 0.452, P<0.001). CONCLUSIONS: In accordance with studies conducted in adults, our results confirm that sprint performance in adolescents was partially dependent %FFM. The main finding was that ICW was a significant predictor of sprint in adolescents
Published Abstract in Medicine and Science in Sports and Exercise, 46(5S): 685. G-28 Thematic Poster - Fitness Assessment and Training in Young Athletes.
Keywords: Cuerpo humano - Composición; Hidratación; Body composition; Fat-free mass; Sprint performance; Adolescents; Intracellular water